Effect of Temperature and Water Potential on Sprout Vigor of Potato (Solanum tuberosum L.) Seed Tuber - Ifayanti Ridwan; Phil H. Brown; Shaun N. Lisson; Cri Wahyuni (Hasanuddin University, 2014)
A study was conducted to examine sprouting on potato seed tuber over a range ofdifferent temperature and moisture conditions. The Experiment was conducted under controlledenvironment conditions using a Terratec thermo-gradient table at the School of AgriculturalScience, University of Tasmania. The trial involved exposing seed tubers cv. Russet Burbank(grade 40-60 g) sourced from one seed lot to three water potentials (-0.6 MPa, -0.02 MPa and-0.01 MPa) at each of four different temperatures (10, 15, 20 and 25 °C). The growth mediumused in the trial was vermiculite (Grade 2, Australian vermiculite and Perlite Co-P/L). Thewater potential treatments were prepared based on the relationship of water content and waterpotential by Whalley et al. (2001). Four seed tubers were planted in each container filled withgrowth medium at a 10 cm depth and covered by the growth medium before the containerswere resealed. Using a pseudo replication design with temperature as the block, the moisturetreatments were randomized within each temperature treatment with two replicate containersfor each treatment combination. The design therefore provided a total of 8 tubers for eachtemperature and water potential combination, and a total of 24 treatment combinationsoverall. An analysis of variance and least significant difference (LSD) procedure using SPSSfor windows version 14.0 was performed to determine the response of the tuber seeds totemperature and moisture. Temperature and moisture significantly affected sprout growthrate, assessed as the sprouting capacity of the tubers (FW sprouts per FW tubers). Sproutingcapacity of seed tubers increased with increasing temperature and water potential. Therewas a significant interaction between temperature and moisture treatments on the sproutingcapacity (p<0.05). The differences between water potential treatments were greater at highertemperature, with differences between sprouting capacity of tubers exposed to dry and wetconditions particularly evident at temperatures of 20 and 25 ºC. Relation between the resultand risk in plant response to warmer climate as an impact of global warming is discussed.